2020
DOI: 10.1002/ps.6132
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the binding ability of the odorant binding protein BminOBP9 of Bactrocera minax to citrus volatiles

Abstract: BACKGROUND Bactrocera minax, one of the most important citrus pests, oviposits exclusively on citrus fruit. In the insect olfactory system, odorant‐binding proteins (OBPs) facilitate the initial recognition role of host odor molecules. The aim of this study was to characterize the functional OBPs of B. minax and identify specific volatile organic compounds in the Citrus genus as OBP targets. RESULTS BminOBP9 (BminGOBP99a), a closely related homolog of BdorGOBP99a, which reduces the egg‐laying behavior of Bactr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 70 publications
(149 reference statements)
1
13
0
Order By: Relevance
“…OBPs participating in the perception of these odorants have been progressively identified. It has been documented that CvesOBP1, CvesOBP4, and BminOBP9 identified from B. minax showed high affinity for β-caryophyllene in an in vitro binding assay [122,124]. Furthermore, BdorOBP84a-1, identified from B. dorsalis, also showed moderate affinity to several volatiles, including 1-octen-3-ol [117].…”
Section: Obpsmentioning
confidence: 99%
See 4 more Smart Citations
“…OBPs participating in the perception of these odorants have been progressively identified. It has been documented that CvesOBP1, CvesOBP4, and BminOBP9 identified from B. minax showed high affinity for β-caryophyllene in an in vitro binding assay [122,124]. Furthermore, BdorOBP84a-1, identified from B. dorsalis, also showed moderate affinity to several volatiles, including 1-octen-3-ol [117].…”
Section: Obpsmentioning
confidence: 99%
“…Additionally, several OBPs have been reported to have a strong affinity for several common host volatiles. Research on BminOBP9 (BminGOBP99a) of B. minax showed that it bound not only to β-caryophyllene but also to other citrus volatiles, such as ocimene and myrcene [124]. It was also observed that BdorOBP99b (BdorOBP99a) of B. dorsalis had a high affinity for host volatiles, such as ocimene and limonene [124].…”
Section: Obpsmentioning
confidence: 99%
See 3 more Smart Citations